The ‘Bracaraugustani’ and the epigraphy monuments: an analysis of the female presence in the inscriptions of ‘Bracara Augusta’ - Gomes, Raquel de Morais Soutelo (Romanitas - Revista de Estudos Grecolatinos, 2015)
Founded at the end of the 1st century BC, Bracara Augusta, capital of the conuentus Bracaraugustanus was a dynamic city, with important administrative, juridical and religious functions. Its population formed by the various members of the hillforts that surrounded it, lived in an urban space, designed to follow Roman patterns, and adopted some of the Roman habits, like their cultural impulse to produce inscriptions. The products of this Roman custom are analyzed in this article, in search of a better understanding of the women that lived there, observing data that mentioned how they were presented, what was their social status and their activities in this community and also how they were remembered by their loved ones.
Keywords: Bracara Augusta; Epigraphic habit; Gender